Jet-based bioprinting of viable human cells (Transactions on Additive Manufacturing Meets Medicine, 2022)
This work demonstrates that viable human cells may be deposited in predefined geometries by an HP (HP inc.) TIPS (Thermal Inkjet Pipette System) jet-based bioprinter. The aim of these experiments is the incipient use of this bioprinter for printing human cells and verification of the cell viability following printing. Human embryonic kidney (HEK) cells were suspended in a modified cell medium to form a bioink-- a suspension of cells in a carrier solution for use in jet-based bioprinting. Cells were marked using Calcein dye, a cell-permeant dye used to determine cell viability via fluorescence. 1 cm x 1 cm squares were printed into 6-well plates using the jet-based bioprinter. Fluorescence images show a cell viability of over 90% immediately post-print. Printed cells reached approximately 70-100% confluence per well five days post printing. To offer the print more structural support, bioink was printed in alternating layers with a hydrogel, creating a cell-laden three-dimensional biological structure.
Keywords: Bioprinting; Hydrogel; Jet-based bioprinting; bioink; biofabrication; tissue engineering